The logical-mathematical model of career success: the analysis of indicators of professional success of employees in a sales company - Kononov, Aleksandr N.; Klimova, Elena M. (International Journal of Psychosocial Rehabilitation, 2020)
The significance of the problem presented in the article is explained by the fact that the increasing level of professional performance success of employees of a sales organization in terms of rapidly changing Russian economy, as part of the world economic system, has a direct impact on the stability of the enterprise.The purpose of the article is to develop a logical-mathematical model and to determine the factors that affect the success level of professional performance of sales company employees.The major methodology applied in the research is the mathematical modeling method carried out by means of the discriminant analysis, which was implemented in order to discover the criteria that significantly divide employees into the successful and unsuccessful ones based on their level of professional success, as well as to develop a logical-mathematical model of the career success of sales companies' employees.The structure of the logical-mathematical model of performance success of sales company employees includes one main as well as two additional formulas, in which the substitution of the values of the corresponding indicators of professional success results in the definition of a level of career success of employees of a trade organization.The logical-mathematical model is aimed to elaborate on the key indicators that significantly affect the success of professional performance of trade companies' staff members, in relation to which the company psychological department workers (HR managers, business coaches) increase the performance level of employees who demonstrate a low degree of professional ptoductivity.